Morphological approach in creative requirements elicitation from crowdsourcing - Tuan Mohd Amin, Tengku Azharuddin (2017)
Creativity is a subject that gained increasing interest in requirements engineering field. Creative-based requirements elicitation helps in generating requirements in original and innovative ways. Lately, crowdsourcing has been emerged in requirements elicitation after realizing the benefits of crowd. Crowdsourcing allows a wide diversity of stakeholders able to express their perceptions about product. However, to analyze the large amount of ideas from crowd would be a great challenge. This work focuses on how creative ideas gathered and analyzed from the crowd using morphological approach in deriving requirements for the software product. In addition, the approach encourages collaboration between crowd and requirements engineers in order to elicit creative ideas for producing an innovative software product. In this study, a prototype is developed to evaluate the proposed approach. The prototype assists requirements engineer to produce creative and innovative solutions from the ideas elicited from the crowd. Based on the results, it shows that the use of text mining to build morphological matrix can provide a large number of potential creative requirements that cannot be easily captured by requirements engineer.